2021
DOI: 10.1002/glia.24080
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase plasminogen activator mediates changes in human astrocytes modeling fragile X syndrome

Abstract: The function of astrocytes intertwines with the extracellular matrix, whose neuron and glial cell-derived components shape neuronal plasticity. Astrocyte abnormalities have been reported in the brain of the mouse model for fragile X syndrome (FXS), the most common cause of inherited intellectual disability, and a monogenic cause of autism spectrum disorder. We compared human FXS and control astrocytes generated from human induced pluripotent stem cells and we found increased expression of urokinase plasminogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…The biological process pathways enriched in the GO analysis were also found related to the FXS. For instance, extracellular structure plays a pivotal role in neurite outgrowth, neural connectivity, and synaptic plasticity (Cope and Gould, 2019;Peteri et al, 2021). Alterations in connected tissue and extracellular matrix (ECM) have been implied in the pathophysiological development of FXS (Ramírez-Cheyne et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The biological process pathways enriched in the GO analysis were also found related to the FXS. For instance, extracellular structure plays a pivotal role in neurite outgrowth, neural connectivity, and synaptic plasticity (Cope and Gould, 2019;Peteri et al, 2021). Alterations in connected tissue and extracellular matrix (ECM) have been implied in the pathophysiological development of FXS (Ramírez-Cheyne et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One group recently published a method to generate astrocytes with forebrain patterning from hPSCs (hASTRO) [ 144 ]. Using this method, the group found that the expression of urokinase plasminogen activator (uPA), a protease that regulates the degradation of the extracellular matrix, was increased in FXS hASTRO compared to control hASTRO [ 145 ]. Interestingly, the increase in uPA level was correlated with a reduced intracellular calcium response to depolarization in hASTRO [ 145 ], which is in contrast to the enhanced intracellular calcium release seen in FXS NPCs [ 63 ].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Using this method, the group found that the expression of urokinase plasminogen activator (uPA), a protease that regulates the degradation of the extracellular matrix, was increased in FXS hASTRO compared to control hASTRO [ 145 ]. Interestingly, the increase in uPA level was correlated with a reduced intracellular calcium response to depolarization in hASTRO [ 145 ], which is in contrast to the enhanced intracellular calcium release seen in FXS NPCs [ 63 ]. The authors stated that uPA signaling could play a role in modulating synaptic excitation/inhibition balance found to be altered in FXS [ 146 ].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Human forebrain astrocytes were produced as described previously 91 from male FXS (HEL69.6, HEL70.3, HEL70.6, and HEL100.2) and control (HEL23.3, HEL24.3, HEL46.11, PO2/UEF-3A, and PO4/UEF-3B) human iPSC lines reported in several previous studies [92][93][94][95][96][97][98] . The research using human cells was approved by the Ethics Committee of the Hospital District of Helsinki and Uusimaa, Finland.…”
Section: Human Astrocytesmentioning
confidence: 99%